The negative effects of oppression in the recovery process. Issue 1 (2nd January 2017) - Timander, Ann-Charlott; Möller, Anders; Davidson, Larry
ABSTRACT: The aim of this project was to study if and how experiences of oppression on the grounds of mental distress and gender affect the reclaiming and (re)construction of identities in the recovery process. In this study 33 narratives were analysed using framework analysis. The analysis showed that the experience of oppression affected the participants negatively along emotional and psychological pathways and affected their life activities, that is, their recovery process was negatively affected. By using a British disability studies perspective on oppression [Thomas, C.2010 . "Medical Sociology and Disability Theory." In New Directions in the Sociology of Chronic and Disabling Conditions. Assaults on the Lifeworld, edited by G. Scambler, and S Scambler, 37–56. Palgrave Macmillan] the understanding of experiences of mental distress and recovery was argued to be deepened. The process of recovery was in the light of the findings argued to be a highly social and not just an individualistic process, where social factors like experiences of oppression could become a barrier in the recovery process.